Technological Pedagogical Content Knowledge (TPACK) Teacher in Teaching Geometry in Grade V Elementary School - Aulia Nurdin, Fitri; Fithriani Saleh, Sitti; Kristiawati (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This study aimed to determine the level of Technological Pedagogical Content Knowledge (TPACK) of fifth-grade teachers at Ma’rang District, Pangkep Regency, particularly on geometry. This research uses the descriptive qualitative type of research. The participants were three fifth-grade teachersfrom SD Negeri 6 Pitue, SD Negeri 13 Padang Lampe, and SD Negeri 20 Alesipitto. These schools were chosen because they were once the targets of the Kampus Mengajar Program, while one of the program’s activities was to assist in adapting technology in schools. The data collection used observation and interview techniques. The data analysis consists of data condensation, data presentation, and conclusion. The research results show that the teacher occasionally delivered geometry subject matter using technological devices such as a laptop and projector, as well as the Microsoft PowerPoint application. The use of technological devices and applications in learning was based on teachers’ consideration to make the lessons enjoyable and easy to understand by the students. The teachers also used WhatsApp social media to facilitate communication with students and parents. The obstacles to using technology in learning were the internet network which was not good enough and technological tools that were broken or even non-existent. The teachers’ consideration of the proper use of media in learning shows that teachers had good pedagogical and content knowledge, even though they had not optimally utilized technology. The TPACK of the teachers, especially in geometry, is still at the recognizing level.